(untitled) (Research, Society and Development, 2022)
Objective: Perform a comparative analysis of the healing process of burns in Swiss mice treated with silver sulfadiazine 1% and honey. Methods: The 2nd degree burns were caused by the technique of heated plate at 100°C. After the injury, the treatment of the groups treated with 1% Silver Sulfadiazine and honey from bees of the species Tetragonisca angustula was performed, the microscopic analysis was done by Hematoxylin/Eosin (HE) and PicroSirius techniques. Results: The macroscopic analysis indicated retraction of the lesion in a similar way in both treatments, revealing no significant differences related to the established time and an increase in healing, the microscopic data showed better healing with Silver Sulfadiazine 1%. Conclusion: The use of honey as a healing agent was close to the comparative parameters of the study with Silver Sulfadiazine 1%.